Samproduksjon i forskning Forskning med nye aktører - Sigrid Østensjø (Scandinavian University Press (Universitetsforlaget), 2019)
Reserachers and users of public health and welfare services are increasingly expected to actively collaborate in research efforts. The purpose of this volume is to provide critical reflections on user participation in research on health and welfare services. The book addresses a range of questions - why has user participation become such an important issue? Who are defined as "users", and how should we understand notions like "collaboration" and "participation"? Which opportunities, challenges and dilemma occur as consequences of user collaboration and participation in research? And does user involvement increase the quality and relevance of research efforts? The majority of the chapters in this volume present findings from research projects where user participation and collaboration has been a core concern. The remaining chapters address general methodological and ethical questions and issues - how different forms of knowledge can find their place within a user participation paradigm, and how research quality can be construed and evaluated. The book is written for researchers, ph.d.- and graduate students, but also for users and staff in the health and welfare services addressed in the book.